Outdoor kids in an inside world : getting your family out of the house and radically engaged with nature - Rinella, Steven (Random House, 2022)
"The average American spends ninety percent of their time indoors, and children are no exception. Today, kids can spend up to seven hours per day looking at screens. Not only does this phenomenon have consequences for our kids' physical and mental health, it calls into question their ability to understand and engage with anything beyond the built environment. We can talk about environmental stewardship, but until more people make meaningful contact with nature, the welfare of our planet is in jeopardy. Thankfully, with the right mindset, families can find beauty, meaning, and connection in a life lived outdoors. Now, outdoors expert Steven Rinella shares the parenting wisdom he has garnered as a father whose family has lived amid the biggest cities and wildest corners of America. Throughout, he offers practical advice for getting your kids radically engaged with nature in a muddy, thrilling, hands-on way, guided by black-and-white illustrations throughout-with the ultimate goal of helping them see their own place within the natural ecosystem. No matter their location-rural, suburban, or urban-caregivers and kids will bond over activities such as: Camping to conquer fears, build tolerance for dirt and discomfort, and savor the timeless pleasure of swapping stories around a campfire. Growing a vegetable garden to develop a capacity to nurture and an appreciation for hard work. Foraging for wild berries, nuts, and mushrooms as a way to experience the delight of discovery. Fishing local lakes and rivers to learn the value of patience while grappling with the possibility of failure. Cooking together with naturally sourced ingredients you procured. Hunting for sustainably managed wild game to face the realities of life, death, and what it really takes to obtain our food"--